2011
DOI: 10.1302/0301-620x.93b7.26105
|View full text |Cite
|
Sign up to set email alerts
|

The surgical treatment of anterior column and anterior wall acetabular fractures

Abstract: Isolated fractures of the anterior column and anterior wall are a relatively rare subgroup of acetabular fractures. We report our experience of 30 consecutive cases treated over ten years. Open reduction and internal fixation through an ilioinguinal approach was performed for most of these cases (76.7%) and percutaneous techniques were used for the remainder. At a mean follow-up of four years (2 to 6), 26 were available for review. The radiological and functional outcomes were good or excellent in 23 of 30 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Since Letournel 10) introduced the ilioinguinal approach in the 1960s, it has been adopted by many surgeons as the principal anterior surgical approach for the treatment of acetabular fractures for several decades. 3 5 10 11) The classic ilioinguinal approach provides excellent access to the anterior and internal aspects of the entire pelvis and acetabulum. However, most of the complications are related to the neurovascular bundle and lymphatic structures and arise in the intermediate part of the ilioinguinal approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Letournel 10) introduced the ilioinguinal approach in the 1960s, it has been adopted by many surgeons as the principal anterior surgical approach for the treatment of acetabular fractures for several decades. 3 5 10 11) The classic ilioinguinal approach provides excellent access to the anterior and internal aspects of the entire pelvis and acetabulum. However, most of the complications are related to the neurovascular bundle and lymphatic structures and arise in the intermediate part of the ilioinguinal approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, the quality of reduction and clinical results in our series are comparable to those of other studies. 5 17 18) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 Open reduction and internal fixation (ORIF) of fractures, associated with rapid rehabilitation, is considered the ‘benchmark’ for treatment. 4 - 8 Judet et al 2 , 3 , 9 have shown that an anatomical reduction with a gap of 2 mm or less is a predictor of good joint function and reduced risk of post-traumatic osteoarthritis. Therefore, the surgeon should try to obtain reductions with zero displacement or up to 1 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The plate could be placed from the front of the pubic tubercle, the inner side of pubic branch, the inferior border of arcuate line edge, to the sacroiliac joint. It is a perfect fixation route for placing the plate to restore the integrity of the pelvis since it could offer a relative regular and smooth surface with adequate bone thickness [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%